From anthropocentrism to sustaincentrism : case study on beverage companies in India - Shamsi Rizvi, Yasmeen (Array, 2021)
Business organizations have been facing an unprecedented level of criticisms for being one of the prime contributors to the deterioration of environmental health. These criticisms have prompted organizations to make environmental sustainability a part of their business strategy. The case study on the beverage companies show how organizations are making a shift from anthropocentrism to sustaincentrism. Here we have mainly focussed on how PepsiCo and Coca-Cola have transformed their image from the one that contributes to bad health of the environment to the one that operates in an environment-friendly manner and how their environmental strategies have helped them in balancing the needs of stakeholders while earning profits.